Do Fishers Need Enough Insurance to Guarantee Their Business Continuity? Evidence from Vulnerable Small-Scale Fishers - SUHARNO, Suharno; ARIFIN, Agus; YUNANTO, Ary (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022DO - 10.14505/jemt.v13.1(57).09, 2022)
Small-scale fisheries have a profound effect on providing food and employment for millions of the world's population. Small-scale fisheries contribute more than 90 percent of the global catch. Unfortunately, small-scale fishers still live in poverty, and small-scale fisheries more than 95 percent were found in low-income countries. Average productivity that is inefficient, low levels of education, lack of opportunities to access capital, and lack of guarantees and limitations in obtaining social, economic, and political rights result in fishers' vulnerability in all aspects. Efforts to guarantee social, economic rights and subsidies for fishers are critical. This study examines the factors that influence the decision to participate in fisher's insurance, such as income as collateral for fishers during fishing activities, some trips, catch skill, and fishing gear coefficient. Participating in insurance is one form of business-facing uncertainty (season, fish stocks) while hoping for an increase in the sense of security for fishers compared to those who do not participate in insurance. Data processing results using logistic regression analysis showed that the variable income, some trips, catches, and skills had a positive and significant effect, while the fishing gear coefficient variable had no significant effect. This study recommends that local governments pay more/ attention and supervise small fishers' skills in using fishing gear, the number of trips made, and the number of catches that were focusing on adding their income because these four factors determine fishers' insurance continuity.